Optimization of load distribution of initial training sportsmen - Atkociuniene, V.; Atkociunas, V. (Management Theory and Studies for Rural Business and Infrastructure Development, 2019)
Unsystematic training of young sportsmen, sub-optimal distribution of training load creates preconditions for their demotivation and short-term sport performance. The purposefulness of the exercise, consistent and systematic training with regard to social factors and the recommendations of the scientists help to achieve the highest and lasting results. Research object: Kaunas city sports school "Bangputys" the initial preparation of the sportsmen groups annual plans of 2018-2019 years.